The Potential of Transmission in Neonates Born to Mothers Infected with Covid-19 and Its Review According to The Islamic Perspective - Medina Nursalfa, Azzahra; Souvriyanti, Elsye; Arsyad, Muhammad (Fakultas Kedokteran Universitas YARSI, 2024)
Coronavirus Diseases 2019 (COVID-19) is a new type of disease that occurs in humans, has a causative agent, namely the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Transmission of COVID-19 can occur through droplets and close contact with infected patients. Groups that can be at risk of infection are the elderly and patients with certain medical conditions. Meanwhile, transmission of respiratory viral infections is rare intrauterine. There was two reported cases explaining the possibility of congenital infection in two neonates within 48 hours after birth in the isolation of COVID-19 from the amniotic fluid, placenta, and nasopharynx. This research is a descriptive study with quantitative data collection and cross sectional design. The sample of this study was neonates born to mothers infected with COVID-19 at Yarsi Hospital and Pertamina Jaya Hospital Jakarta. The results showed that there was a 1.4% potential for transmission. As many as two out of 139 neonates born to infected mothers experienced COVID-19 transmission. As a result of being infected with COVID-19 the maternal mortality rate is 1.4% and for neonates 1.4%. Vertical transmission of COVID-19 from infected pregnant women to neonates has little potential. Nevertheless, prevention must still be carried out so that transmission does not occur and has a major impact on the mother and baby.